2019
DOI: 10.1109/access.2019.2921411
|View full text |Cite
|
Sign up to set email alerts
|

Path Loss Predictions in the VHF and UHF Bands Within Urban Environments: Experimental Investigation of Empirical, Heuristics and Geospatial Models

Abstract: Deep knowledge of how radio waves behave in a practical wireless channel is required for effective planning and deployment of radio access networks in urban environments. Empirical propagation models are popular for their simplicity, but they are prone to introduce high prediction errors. Different heuristic methods and geospatial approaches have been developed to further reduce path loss prediction error. However, the efficacy of these new techniques in built-up areas should be experimentally verified. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 51 publications
2
63
0
Order By: Relevance
“…for Terrain type C where, frequency (f) measured in MHz and hr is the Customer Provided Equipment antenna height in meters. In this paper, the SUI model is considered to predict the path loss in entirely selected environments, namely suburban and urban [20], [21]. Due to the two models (COST-231 Hata model and SUI) integrated with measurement data have concentrated on these issues notified that, wireless communication has a strong potential prediction to improve the received signal indicators (RSSI).…”
Section: ) Stanford University Interim (Sui) Modelmentioning
confidence: 99%
“…for Terrain type C where, frequency (f) measured in MHz and hr is the Customer Provided Equipment antenna height in meters. In this paper, the SUI model is considered to predict the path loss in entirely selected environments, namely suburban and urban [20], [21]. Due to the two models (COST-231 Hata model and SUI) integrated with measurement data have concentrated on these issues notified that, wireless communication has a strong potential prediction to improve the received signal indicators (RSSI).…”
Section: ) Stanford University Interim (Sui) Modelmentioning
confidence: 99%
“…It was concluded that the COST 231-Hata and Ericson models showed the best performance in urban and suburban areas. Recent works in [16] also compared the efficiencies of empirical, heuristic, and geospatial methods used for signal path loss predictions using data collected in urban Nigerian cities to develop path loss models. The developed models and empirical models were compared with field measured data.…”
Section: Related Workmentioning
confidence: 99%
“…Path loss for this model is given in (16) as presented in [22] PL SUI = A +10g log( f is the frequency in MHz…”
Section: Stanford University Interim (Sui Model)mentioning
confidence: 99%
“…Popoola et al proposes heuristic methods, geospatial and stochastic channel models to predict PL in the VHF and UHF bands for specified routes. The comparative analysis shows that ANN-based PL model has better prediction accuracy and generalization ability than stochastic channel models [36]- [38].…”
Section: Introductionmentioning
confidence: 99%